2015
DOI: 10.1590/0100-69912015001010
|View full text |Cite
|
Sign up to set email alerts
|

Use of the amniotic membrane to cover the peritoneal cavity in the reconstruction of the abdominal wall with polypropylene mesh in rats

Abstract: Use of the amniotic membrane to cover the peritoneal cavity in the reconstruction of the abdominal wall with polypropylene mesh in rats Use of the amniotic membrane to cover the peritoneal cavity in Use of the amniotic membrane to cover the peritoneal cavity in Use of the amniotic membrane to cover the peritoneal cavity in Use of the amniotic membrane to cover the peritoneal cavity in Use of the amniotic membrane to cover the peritoneal cavity in the reconstruction of the abdominal wall with polypropylene the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Vascular formation was more significant in the animals that received the HAM, indicating that even its conservation at lower temperatures does not inactivate proangiogenic substances previously identified in the cryopreserved membrane 26 . In addition, the harvesting of the amniotic membrane does not offer any risk to the newborn or the parturient, and the membrane can be easily obtained and stored in laboratories for later use.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Vascular formation was more significant in the animals that received the HAM, indicating that even its conservation at lower temperatures does not inactivate proangiogenic substances previously identified in the cryopreserved membrane 26 . In addition, the harvesting of the amniotic membrane does not offer any risk to the newborn or the parturient, and the membrane can be easily obtained and stored in laboratories for later use.…”
mentioning
confidence: 80%
“…We emphasize that the use of the HAM offers the advantages of high availability, ease of application, and good storability [12][13][14][15][16][17][18] . In this context, it is possible to affirm that by presenting properties that favor the re-structuring of the damaged portions of the tissues, the amniotic membrane could be used as a biological coverage of acute and chronic wounds [18][19][20][21][22][23][24][25][26] .…”
mentioning
confidence: 97%
“…The impact of meloxicam on the inflammatory stage in this study was not significant, perhaps because it is preferential to the inhibition of cyclooxygenase-2, which is believed to be inductive in tissue injuries and at the same time does not inhibit the cicloxigenases, behaving only like a modulating drug 12,38,41,42 .…”
Section: Discussionmentioning
confidence: 60%
“…However, there are limited studies on the use of AM in reconstruction of abdominal wall, all of which were experimental animal studies with conflicting outcomes (6,(25)(26)(27). The majority of these studies showed that AM is an effective antiadhesive barrier in polypropylene mesh repair of abdominal wall hernia (6,25,26). polypropylene mesh alone for the correction of abdominal wall defect in rats.It was found that although AM application did not alter the formation of adhesions after the first week of operation, it accelerated the healing as shown by increased inflammation and angiogenesis activity.…”
Section: Discussionmentioning
confidence: 99%